Evaluation of photocatalysis as pre-treatment method for rubber glove wastewater reclamation system: article - Suaid, Suhada; Lim, Ying Pei (2019)
The aims of this study were to characterize the rubber glove wastewater and investigate the use of Ti0₂ as photocatalyst for pre-treatment of rubber glove wastewater reclamation system. Three parameters, i.e.; Ti0₂ loading, pH and light sources were varied to evaluate the performance of photocatalyst for chemical oxygen demand (COD) removal in rubber glove wastewater. The photo-degradation experiment was carried out for the duration of 45 minutes inside a dark box that have been illuminated with aluminium foil and irradiated with UV light. The rubber glove wastewater showed high strength of wastewater which contained major pollutants with high total dissolved solid (TDS) and COD, in the range of 1154-6020 mg/L and 1018-1636 mg/L, respectively. The optimum Ti0₂ loading in treating rubber glove wastewater was at 0.2 g/L with maximum removal of COD at 44.65%. Within the range of pH tested (pH 4- pH 9), the highest COD removal was observed at pH 7 (neutral). Photo-degradation process under UV light irradiation showed greater COD removal at 44.65% compared to 17.7%) under solar irradiation. Thus, in this study, pre-treatment of rubber glove wastewater using Ti0₂ as photocatalyst shows promising result in terms of COD removal for rubber glove wastewater.